Prediction of CBR Value from Index Properties of Cohesive Soils. - M. E. Zumrawi, Magdi (University of Khartoum Engineering Journal, 2022)
The aim of this paper is to develop empirical relationship between CBR values and soil index properties of cohesive soils as road subgrade. However; it is always difficult for highway engineers to obtain representative CBR values for design of pavement. Over the years, many correlations had been proposed by various researchers in which the soil index properties were used to develop these correlations. The CBR value is affected by the initial state parameters of soil as described by the water content and dry density and the testing conditions. Silty clay soil samples were compacted at different water contents and dry densities to measure the strength by CBR tests in soaking and unsoaking conditions. The results show that the CBR values of these soils are greatly influenced by the water content and dry density (i.e. the initial state parameters) of the soil as well as the testing conditions. Analysis of the experimental data indicated that it is possible to combine these initial state parameters in a way reflecting the influence of each of them on the CBR. Therefore a new concept has been developed; this is called the initial state factor. This factor is also developed for the soaking or saturated condition and is called the soaking state factor. On basis of this concept, a reliable strong correlation has been established between CBR values and soil state factors and plasticity index. Comparison between the measured soaked or unsoaked CBR values and the calculated results using the developed equations clearly indicates the reliability of these equations